CO2 adsorption on carbonaceous surfaces:a combined experimental and theoretical study (2003)
ABSTRACT: We present an experimental and theoretical study to provide further insight into the mechanism of CO chemisorption on 2 carbonaceous surfaces. The differential heat of CO adsorption at low and high coverages was determined in the temperature 2 range 553–593 K. We found that the heat profile has two distinct energetic zones that suggest two different adsorption processes. In the low-coverage region, the heat of adsorption decreases rapidly from 75 to 24 kcal/mol, suggesting a broad spectrum of binding sites. In the high-coverage region, the heat becomes nearly independent of the loading, from 9 to 5 kcal/mol. A systematic molecular modeling study of CO chemisorption on carbonaceous surfaces was performed. Several 2 of the carbon–oxygen complexes that have been proposed in the literature were identified and characterized. The calculated adsorption energies are within the experimental uncertainty of the heat of adsorption at low coverage. Pre-adsorbed oxygen groups decrease the exothermicity of CO adsorption. In the high-coverage region, our theoretical results suggest that CO 2 2 molecules are likely to adsorb on surface oxygen complexes and on graphene planes.  2003 Elsevier Science Ltd. All rights reserved.